2003
DOI: 10.1063/1.1566473
|View full text |Cite
|
Sign up to set email alerts
|

Phonon spectrum and thermal properties of cubic Si3N4 from first-principles calculations

Abstract: The phonon spectrum of cubic Si 3 N 4 was calculated by first-principles techniques. The results permit an assessment of important mechanical and thermo-dynamical properties such as the bulk modulus, lattice specific heat, vibration energy, thermal expansion coefficient, and thermal Grüneisen parameter for this compound. The calculated phonon spectrum shows a gapless spectrum extending to a cutoff energy of ϳ1030 cm Ϫ1 . The calculated Raman-and infrared-active phonon frequencies are compared with measured dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
23
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 42 publications
(27 reference statements)
12
23
1
2
Order By: Relevance
“…Overall, our calculation is in better agreement with the experimental data of Paszkowicz et al 40 , and the the- oretical data of Fang et al 41 The calculation reported by Paszkowicz et al, which is based a simplified Debye model to approximate the phonon density of states, 40 is consistent with our data at temperatures below 500 K. However, their predicted TEC at high temperatures is apparently lower than all other three calculations that are based on the first-principles phonon density of states. At low temperatures, the prediction of γ-Si 3 N 4 from Kuwabara et al is noticeably larger than other calculations, including ours.…”
Section: -36supporting
confidence: 81%
See 1 more Smart Citation
“…Overall, our calculation is in better agreement with the experimental data of Paszkowicz et al 40 , and the the- oretical data of Fang et al 41 The calculation reported by Paszkowicz et al, which is based a simplified Debye model to approximate the phonon density of states, 40 is consistent with our data at temperatures below 500 K. However, their predicted TEC at high temperatures is apparently lower than all other three calculations that are based on the first-principles phonon density of states. At low temperatures, the prediction of γ-Si 3 N 4 from Kuwabara et al is noticeably larger than other calculations, including ours.…”
Section: -36supporting
confidence: 81%
“…Our zero-pressure results are compared with available experimental data [33][34][35][36][37][38][39][40] and previous calculations. 21,22,41,42 Conclusions are drawn in Sec. IV.…”
mentioning
confidence: 99%
“…It has a hardness comparable to the hardest known oxide (stishovite, a high-pressure phase of SiO 2 ) [2][3][4][5][6] and significantly greater than the hardness of α-and β-Si 3 N 4 [7]. In recent years, many experiments on the properties of Si 3 N 4 have been performed, and their theories have been studied [8][9][10][11][12][13][14][15][16][17][18]. Among all the properties of Si 3 N 4 studied so far, the thermodynamic properties have been an intriguing subject.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ab initio calculations have been performed to calculate infrared and Raman phonon modes at the zone centre by Pascal and Gervais [14] and Wijs et al [15] for MgAl 2 O 4 and by Fang et al [16] for cubic Si 3 N 4 . Very recently, the ab initio technique has been used to calculate the lattice dynamical properties of LiMn 2 O 4 by Fang et al [17].…”
Section: Introductionmentioning
confidence: 99%